Complement membrane attack complex stimulates production of reactive oxygen metabolites by cultured rat mesangial cells. - Adler, S (1986)
To explore possible mechanisms by which complement membrane attack complexes (MAC) that are deposited in the glomerular mesangium might be pathogenic, we stimulated rat glomerular mesangial cells grown in vitro with nascent MACs formed from the purified human complement components C5b6 and normal human serum and measured production of superoxide ion (O2-) and hydrogen peroxide (H2O2). Mesangial cells incubated with C5b6 + serum, which results in cell membrane interaction with the MAC, produce 0.9 +/- 0.15 nmol O2-/10(5) cells per 30 min, which was significantly greater than the amount produced by cells incubated with C5b6 alone, serum alone, or decayed MACs that can no longer interact with the cell membrane (0.3 +/- 0.2, 0.4 +/- 0.1, 0.3 +/- 0.2 nmol O2-/10(5) cells per 30 min, respectively; P less than 0.02). Production of O2- after stimulation with MACs increased during the first 20 min of incubation but then plateaued. Cells exposed to decayed MACs produced small amounts of O2-, which did not increase from 20 to 60 min. Production of H2O2 was also observed after stimulation with MACs, and continued to increase during 60 min of incubation (1.22 +/- 0.16 nmol H2O2/10(5) cells per 60 min), whereas H2O2 production could not be detected after exposure to decayed MACs. Cell viability was not adversely affected by exposure to nascent MACs as determined by trypan blue exclusion or chromium-51 release. These results demonstrate that glomerular mesangial cell membrane interaction with the MAC stimulates the production of the toxic oxygen metabolites O- and H2O2. Activation of the terminal complement pathway by mesangial immune deposits in vivo might lead to tissue injury by stimulation of local production of toxic oxygen-free radicals.